Exploring the Role of Social Media Use and Knowledge Management in Enhancing Competitive Performance: The Mediating Effect of Open Innovation Capability and Innovativeness - Aryan Nassiri (Journal of Advanced Research in Social Sciences and Humanities, 2024)
Aim: Is this study investigates the potential direct and indirect effects of social media use, knowledge management, and innovation concepts (open innovation and innovativeness) on nonprofit sports teams’ competitive performance. Methodology: 342 authentic surveys were gathered online from Iranian nonprofit sports club board members. To examine the connections between variables, structural equation modelling was employed. Findings: The findings show that knowledge management and social media use improve competitive performance through two distinct sequential mediators: innovativeness and open innovation. Implications/Novel Contribution: Nonprofit sports organisations should benefit from encouraging social media use and knowledge management by, for example, allowing the creation and dissemination of new knowledge by utilising both internal and external knowledge sources. Sports teams can improve their ability to use outside information and cultivate a positive outlook on novelty and creativity by doing this, which will enable them to innovate more and perform better. The study offers managerial and theoretical ramifications that support sports teams in improving many facets of their organisational performance and innovating.